Introduced marine crab species in the northern Baltic Sea : from detection to impacts - Forsström, Tiia (fi=Turun yliopisto|en=University of Turku|, 2017)
Human mediated species introductions are often irreversible, represent a world-wide problem and are considered one of the threats to marine biodiversity. Invasions can have an impact on the native species and communities, but invasions also affect the demography, dynamics, and genetic composition of the invading species population. Thus, newly introduced species provide a unique opportunity to study different ecological and genetic processes associated with invasions, such as invasion dynamics, build-up of the spatial and temporal population genetic structure, understanding the roles of added or removed functions in an ecosystem and the direct impacts of the invaders. In my thesis, I studied population demography, dynamics, and the genetics of a newly introduced mud crab, Rhithropanopeus harrisii, in the Archipelago Sea in the northern Baltic Sea. In addition, I studied the impacts of this novel invader to the native species and tested whether new molecular tools could be used to detect and monitor this newly introduced species. The results show that R. harrisii has established a relatively stable reproductive population in the invaded area, has spread along the coast, and can be found in several habitats that range from soft sediments to the macroalga Fucus vesiculosus having negative impacts on the abundance, richness, and diversity of its prey species. The abundance of the introduced population in the Archipelago Sea is lower than in its native range of North America, although the individuals grow substantially larger in the northern Baltic Sea increasing the reproductive output. The overall abundance of R. harrisii appeared to follow the boom and bust pattern with a rapid initial abundance increase and subsequent decline. The population dynamics of R. harrisii was mainly driven by changes in the survival of the reproductive females. In addition, environmental variables, such as temperature, was related to the recruitment and growth of juveniles, thus indicating that increasing temperature caused by climate change could potentially increase juvenile recruitment in the future. There was no significant spatial genetic divergence within Finland, which probably reflects the short invasion history of the species in the area. However, the presence of a significant temporal variation between the cohorts (juvenile vs. adult) indicated a lack of temporal stability in this species. Finally, a molecular environmental DNA (eDNA) approach can be used to detect R. harrisii from water samples although the detection rate was fairly low. Therefore, more studies are needed to optimize the eDNA method and to evaluate its usability in monitoring. In conclusion, R. harrisii has established a population in the northern Baltic Sea having a negative impact on the native species and communities. However, despite the initial population size increase, the population has declined to the similar size where it was at the beginning of the six-year monitoring. Although the population size seems to be stabilized at the monitoring sites, R. harrisii continues to expand its distribution range, and the rapid initial population increase together with the negative impacts, is likely occurring at the newly invaded sites. The results of my thesis provide new information about the population ecology and genetics of a newly introduced functionally novel species that can be used for further research and management purposes in the future.

Ihmistoiminnan aiheuttamat vieraslajien leviämiset ovat peruuttamattomia sekä maailmanlaajuinen ongelma, ja siksi vieraslajeja pidetäänkin yhtenä uhkana merien monimuotoisuudelle. Vieraslajit voivat vaikuttaa paikalliseen lajistoon ja yhteisöihin, mutta vieraslajien kulkeutuminen vaikuttaa myös vieraslajiin itseensä; sen populaatiorakenteeseen ja -dynamiikkaan sekä populaation geneettiseen rakenteeseen. Siksi hiljattain levinneet vieraslajit luovat ainutlaatuisen mahdollisuuden tutkia vieraslajien ekologisia ja geneettisiä prosesseja, kuten vieraslajien populaatiodynamiikkaa, populaation geneettisen rakenteen alueellista ja ajallista muuttumista sekä vieraslajien vaikutuksia paikalliseen lajistoon. Väitöskirjassani tutkin Saaristomerellä, pohjoisella Itämerellä, hiljattain havaitun vieraslaji liejutaskuravun Rhithropanopeus harrisii populaatiorakennetta, -dynamiikkaa ja populaation geneettistä rakennetta. Lisäksi tutkin kyseisen uudenlaisen lajin vaikutuksia alueen paikalliseen lajistoon sekä kokeilin sopiiko uusi ympäristö-DNA menetelmä vieraslajin havainnointiin ja seurantaan. Tulosteni mukaan liejutaskurapu on vakiinnuttanut paikkansa osana pohjoisen Itämeren eliöyhteisöä, levinnyt uusille alueille ja esiintyy useissa erilaisissa elinympäristöissä, kuten pehmeillä pohjilla sekä rakkoleväkasvustoissa vähentävän saaliikseen käyttämien paikallisten lajien runsautta ja monimuotoisuutta. Pohjoisella Itämerellä liejutaskuravun runsaus on alempi kuin lajin alkuperäisellä esiintymisalueella, mutta Itämerellä yksilöt kasvavat huomattavasti suuremmiksi. Lisääntymisikäisten naaraiden elossa säilyvyydellä oli suurin vaikutus liejutaskuravun populaatiodynamiikkaan kuusivuotisen seurannan aikana. Tämän lisäksi ympäristötekijöistä lämpötila vaikutti poikasten elossa säilyvyyteen ja kasvuun. Ilmastonmuutoksen seurauksena aiheutuva lämpötilan nousu saattaakin parantaa poikasten elossa säilyvyyttä tulevaisuudessa. Saaristomerellä esiintyvillä liejutaskuravuilla ei ollut havaittavissa alueellista geneettistä eriytymistä, mikä selittyy Saaristomeren populaation nuorella iällä. Eri ikäpolvien (poikaset vs. aikuiset) välillä taasen oli merkitsevää vaihtelua geneettisessä monimuotoisuudessa sekä eriytymisessä. Lisäksi totesin, että ympäristö-DNA:han perustavalla menetelmällä pystyy havaitsemaan liejutaskurapuja rapulajia, tosin menetelmä ei vaikuta olevan erityisen herkkä havaitsemaan pohjalla elävää. Lisätutkimuksia tarvitaankin optimoimaan menetelmä sekä arvioimaan sen käytettävyyttä vieraslajien seurannassa. Yhteenvetona, liejutaskurapu on vakiinnuttanut paikkansa osana paikallista lajistoa pohjoisella Itämerellä ja sillä on haitallisia vaikutuksia paikallisiin lajeihin. Kolonisaation alkuvaiheen nopeasta liejutaskurapumäärän kasvusta huolimatta, kuuden vuoden seurannan lopulla rapumäärä oli vähentynyt takaisin lähtötasolle. Vaikka liejutaskurapumäärä näyttää vähentyneen seurantapaikoilla, liejutaskurapu jatkaa leviämistä yhä laajemmalle alueelle pohjoisella Itämerellä ja rapumäärä todennäköisesti kasvaa alkuun voimakkaasti uusilla alueilla aiheuttaen haitallisia vaikutuksia paikalliseen lajistoon. Tulokseni antavat uutta tietoa hiljattain levinneen vieraslajin populaatioekologiasta ja populaation geneettisestä rakenteesta. Tätä tietoa voidaan tulevaisuudessa käyttää tulevien tutkimusten suunnittelussa sekä vieraslajien seurannassa ja torjunnassa.